COVID-19. Volume II, Social consequences and cultural adaptations - Ryan, J. Michael (Abingdon, Oxon ; New York, NY : Routledge, 2021)
The SARS-CoV-2 virus, and the associated COVID-19 pandemic, is perhaps the greatest threat to life, and lifestyles, the world has known in more than a century. The scholarship included here provides critical insights into the institutional responses, communal consequences, cultural adaptations, and social politics that lie at the heart of this pandemic. This volume maps out the ways in which the pandemic has impacted (most often disproportionately) societies, the successes and failures of means used to combat the virus, and the considerations and future possibilities - both positive and negative - that lie ahead. While the pandemic has brought humanity together in some noteworthy ways, it has also laid bare many of the systemic inequalities that lie at the foundation of our global society. This volume is a significant step toward better understanding these impacts. The work presented here represents a remarkable diversity and quality of impassioned scholarship and is a timely and critical advance in knowledge related to the pandemic. This volume and its companion, COVID-19: Volume I: Global Pandemic, Societal Responses, Ideological Solutions, are the result of the collaboration of more than50 of the leading social scientists from across five continents. The breadth and depth of the scholarship is matched only by the intellectual and global scope of the contributors themselves. The insights presented here have much to offer not just to an understanding of the ongoing world of COVID-19, but also to helping us (re-) build, and better shape, the world beyond.
OCLC-licensed vendor bibliographic record.
Keywords: COVID-19 (Disease) -- Social aspects; SOCIAL SCIENCE / Sociology / General